INTEGRATED INITIAL WATER SATURATION MODELING IN GAS RESERVOIR - Nurmida, Arrofi
Initial water saturation holds a significant role to determine hydrocarbon in place and reserve. In the estimation of underground hydrocarbon volume, unrepresentative initial water saturation value certainly results in misleading oil or gas original in place (OOIP/OGIP) with all of its consequences. It is exactly due to this importance that there have been various models in existence at presence to calculate initial water saturation. Due to their large number in existence, it raises a very fundamental question about which of the models is the most valid one, since those independent methods often generate a different value. Realizing the influence of initial water saturation towards reserves and production in the regions, a newly proposed method was built in order to generate more accurate and reliable initial water saturation value. The initial water saturation is calculated by rearranging Brooks-Correy’s parametrical equations to determine capillary pressure synthetic (Pc0) and pore-size distribution exponent (ep) which will be integrated with repeat formation tester, logging, laboratory measurement and finally validated using drill steam test data. On the previous study, this method has already been successfully applied in carbonate and low resistivity reservoir, which shows a very good result. In this study, a method is tested for a gas reservoir to ensure the applicability of this method in many types of reservoir. It is concluded that this method enables every single data to validate each other, and therefore yields a more reliable initial water saturation value.